Snapchat and civic engagement among college students. Issue 2 (3rd April 2019) - Rice, Laurie L.; Moffett, Kenneth W.
ABSTRACT: During the 2016 presidential election cycle, Clinton and Trump used Snapchat as one part of their overall voter outreach and engagement efforts. This portion of their campaign strategy was disproportionately targeted toward younger voters, since those between 18 and 25 comprise a vast portion of Snapchat's user base. Did their efforts, those of political parties, or those of interest groups on Snapchat produce higher levels of civic engagement among college students? We utilize a survey that we conducted from a college campus in the Midwest in October 2016 to answer this question. Using a series of matching analyses, we discover that those students who sent pictures or videos about interest groups, candidates for office, or political parties on Snapchat were more civically and politically active than otherwise similar students who had not participated in these activities.